Assessment of a five-year survival on hemodialysis in Brazil: a cohort of 3,082 incident patients - Matos,Jorge Paulo Strogoff de (2011)
Brazil has the third largest contingent of patients on maintenance hemodialysis (HD) worldwide. However, little is known regarding survival rate and predictors of mortality risk in that population, which are the purposes of this study. A total of 3,082 patients incident on HD, from 2000 to 2004, at 25 dialysis facilities distributed among 7 out of 26 states of Brazil were followed-up until 2009. Patients were 52 ± 16 years-old, 57.8% men, and 20.4%, diabetics. The primary outcome was all causes of mortality. Data were censored at five years of follow-up. The global five-year survival rate was 58.2%. In the Cox proportional model, variables associated with risk of death were: age (hazard ratio - HR = 1.44 per decade, p < 0.0001), diabetes (HR = 1.51, p < 0.0001), serum albumin (HR = 0.76 per g/dL, p = 0.001), creatinine (HR = 0.92 per mg/dL, p < 0.0001), and phosphorus (HR = 1.06 per mg/dL, p = 0.04). The present results show that the mortality rate on HD in this Brazilian cohort was relatively low, but the population is younger and with a lower prevalence of diabetes than the ones reported for developed countries.